Can radiographic plain film be used to determine the depth of the tumour bed in the absence of surgical clips for breast boost planning - Chitapanarux I. (2014)
A number of studies have demonstrated the importance of using surgical clips to define the tumour bed in breast boost radiotherapy. In the absence of such clips, other techniques suggested to improve boost location have included CT and ultrasound (US). Determination of the depth of the tumour bed is important in the selection of electron energy. This study was conducted to prospectively compare the depth of the lumpectomy cavity as defined by ultrasound to radiographic plain film evaluation of the anterior border of the pectoralis muscle.